Pengaruh Edukasi Berdasarkan Teori Efikasi Diri terhadap Kepatuhan Pembatasan Cairan pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RSUP dr M. Djamil Padang - Adep Junika (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
Improper management of fluid restriction in hemodialysis patients can cause interdialytic weight gain which can result in increased mortality and morbidity. It is known that education has been given at the hospital about fluid restriction but non-compliance with fluid intake still occurs, so education based on self-efficacy theory is needed to increase patient confidence in self-management. This study aims to determine the effect of providing education based on self-efficacy theory on compliance with fluid restrictions in hemodialysis patients. This type of quantitative research with a quasi-experimental design pre-test and post-test with control group design. The number of samples in this study was 68 people with the sampling method that is non-probability sampling using purposive sampling technique. The instrument used in data collection was a questionnaire. Data were analyzed through SPSS using the independent t test and paired sample t test. The results showed that there was an effect on adherence to fluid restrictions before and after being given education based on self-efficacy theory p-value 0.000. Providing education based on self-efficacy theory has been shown to increase adherence to fluid restrictions in hemodialysis patients. It is expected that hospitals can apply education based on self-efficacy theory as one of the educational innovations in hospitals